Contributions to the moss flora of Uruguay I: the genus Trachyxiphium (Bryophyta, Pilotrichaceae) - Suarez, Guillermo Martin (2024)
Trachyxiphium, including the species T. guadalupense (Pilotrichaceae), is re-ported for the first time for the moss flora of Uruguay. This study providesa description of its morphological characteristics and highlights its novelhabitat within the region. Additionally, comments and illustrations areprovided.